Recent Developments in the Electroreductive Functionalization of Carbon–Halogen Bonds - Mahanty, Kingshuk; Halder, Atreyee; Maiti, Debabrata; De Sarkar, Suman (Synthesis, 2022)
Electrochemical organic transformations have witnessed significant progress over the past decades owing to their idiosyncratic redox nature. Electrochemistry is globally acknowledged for its sustainability and environmental friendliness, whilst several well-known redox processes are available that do not generate chemical waste or toxic by-products. Apart from this, electrochemistry has adequate potential to steer numerous non-spontaneous reactions, such as cross-coupling, C–C bond cleavage, radical generation, directed C–H functionalization, etc., in a straightforward manner. Beyond electrochemical oxidation reactions, electrochemical reductive transformations have also been enriched in the last few years. Electrochemical reduction can be facilitated by using different strategies, for example, by using a sacrificial electrode or a sacrificial reagent, or can be accomplished in a divided cell. In this short review, different methods for the functionalization of C–halogen bonds, including detailed mechanistic approaches, are discussed.1 Introduction2 Different Strategies for Electrochemical Reduction3 Functionalization of Carbon–Halogen Bonds through Electrochemical Reduction3.1 E lectroreductive Hydrodehalogenation3.2 Electroreductive C–C Coupling of Organohalides3.2.1 Aryl–Aryl C–C Coupling3.2.2 Aryl–Alkenyl C–C Coupling3.2.3 Aryl–Alkyl C–C Coupling3.2.4 Alkyl–Alkenyl C–C Coupling3.2.5 Alkyl–Alkyl C–C Coupling3.3 Electroreductive Coupling of Organohalides with Carbonyls (C=O)3.4 Electroreductive Coupling of Organohalides with Organoboranes4 Conclusion
Keywords: electrochemistry; reduction; organohalide; redox; C–C coupling